Dehydroepiandrosterone Decline in Aging Males as a Predictor of Erectile Dysfunction and Mood Disorders in Patients With Benign Prostate Hyperplasia Undergoing Dutasteride Treatment - Maja Sofronievska Glavinov; Senol Tahir; Stefan Arsov (American Journal of Men's Health)
Age-related decline in dehydroepiandrosterone (DHEA) and its sulfate metabolite, dehydroepiandrosterone-sulfate (DHEAS), affects steroid synthesis in men. DHEA(S) acts as a direct neurosteroid and weak androgen and is the unique steroid unaffected by dutasteride’s inhibitory effect on 5α reductases. This study examined the relationship between dutasteride’s side effects, specifically erectile dysfunction (ED) and mood disorders, and the age-related decline in DHEAS. The study included 250 patients with benign prostatic hyperplasia (BPH), divided into two age groups (<60 and ≥60 years), and treated with tamsulosin or tamsulosin plus dutasteride. DHEAS levels were measured, and patients were assessed for ED and mood disorders using standardized questionnaires. Some patients experienced worsening ED and mood disorders during the 6-month follow-up period. The study found a correlation between DHEAS levels and erectile function and mood status in both age groups receiving dutasteride combination therapy ( p  < .05). Regression analyses showed that DHEAS was a positive predictor for ED in older patients treated with tamsulosin ( p  < .001) and in both age groups receiving dutasteride combination therapy ( p  < .001). In addition, DHEAS was a significant negative predictor for mood changes in both age groups receiving combination therapy ( p  < .001). This study suggests that baseline DHEAS levels can predict changes in erectile function and mood status in BPH patients treated with dutasteride therapy. It is, therefore, recommended to perform DHEAS assessment before starting dutasteride treatment in order to reduce the risk of ED and mood disorders.